PENERAPAN SASTRA LISAN KIAS SATEKHI DITENGAH MASYARAKAT KALIANDA LAMPUNG SELATAN - Aditama, Haryuda; Saputra, Deni wahyu; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study explores kias, a form of oral literature that is part of the traditional oral heritage of the Lampung Sai Batin community, which holds significant cultural, moral, and educational value. Kias is a type of traditional poetic expression that conveys messages of advice, religious teachings, and life values, typically delivered orally during various customary events such as weddings, traditional dances, and social gatherings. However, its use is increasingly marginalized, particularly among the younger generation. The aim of this research is to examine the structure, functions, and potential of kias as a medium for cultural preservation and character education in schools. The findings reveal that kias has a distinctive stanza structure rich in meaning and can be integrated into Lampung language education through interactive and contextual methods. Moreover, kias proves effective in reinforcing moral values, language skills, and cultural identity. Its application in education also encourages students to explore culture, conduct mini-research projects, and engage in creative expression. Therefore, kias serves not only as a preserved cultural heritage but also as a strategic tool in shaping character and fostering young people's appreciation for their local culture.